2022
DOI: 10.1037/neu0000778
|View full text |Cite
|
Sign up to set email alerts
|

The incremental validity of primacy as a predictor of everyday functioning.

Abstract: Objective: Verbal memory is a predictor of later functional deficits. However, it is unclear if a specific aspect of immediate free-recall is driving this relationship. Serial position effects (i.e., relationship between a word’s placement on a word-list and its likelihood of being recalled) have been shown to predict conversion from mild cognitive impairment (MCI) to Alzheimer’s disease (AD). The goal of this study was to determine if serial position effects predict functioning 10-year postbaseline when cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The finding of selective primacy score decline complements existing literature that indicates alterations in serial position effects, mostly primacy performance, can predict future decline in global cognitive functioning among older adults who are considered cognitively normal (Bruno et al, 2013, 2016), those with MCI (Egli et al, 2015), and those with probable AD (Marra et al, 2000). Reduced primacy performance has also been linked with subsequent decline in subjective and performance-based functional measures of daily living in older adults without dementia (Weitzner et al, 2021), providing convergent evidence for the utility of primacy performance in predicting clinically relevant functional changes. Importantly, the primacy score appears to be uniquely suited to differentiating early stage (i.e., MCI (Cunha et al, 2012) or at-risk for AD (La Rue et al, 2008)) groups compared to healthy controls.…”
Section: Discussionmentioning
confidence: 96%
“…The finding of selective primacy score decline complements existing literature that indicates alterations in serial position effects, mostly primacy performance, can predict future decline in global cognitive functioning among older adults who are considered cognitively normal (Bruno et al, 2013, 2016), those with MCI (Egli et al, 2015), and those with probable AD (Marra et al, 2000). Reduced primacy performance has also been linked with subsequent decline in subjective and performance-based functional measures of daily living in older adults without dementia (Weitzner et al, 2021), providing convergent evidence for the utility of primacy performance in predicting clinically relevant functional changes. Importantly, the primacy score appears to be uniquely suited to differentiating early stage (i.e., MCI (Cunha et al, 2012) or at-risk for AD (La Rue et al, 2008)) groups compared to healthy controls.…”
Section: Discussionmentioning
confidence: 96%
“…Although much research has focused on cognitive functioning as a predictor of everyday functioning (including driving) in older adults, [1][2][3][4] increasing evidence suggests there may be utility in measuring everyday functioning as a predictor of cognitive decline and dementia. One longitudinal study found that reported early limitations in everyday functioning especially in instrumental activities of daily living (IADLs) (eg, medication and financial management) was significantly associated with cognitive decline and conversion from normal cognitive ability to MCI.…”
Section: Introductionmentioning
confidence: 99%